Identification of Membrane-Bound Lytic Murein Transglycosylase A (MltA) as a Growth Factor for Francisella novicida in a Silkworm Infection Model - Nakamura, Takemasa; Shimizu, Takashi; Inagaki, Fumiya; Okazaki, Shoma; Saha, Shib Shankar; Uda, Akihiko; Watanabe, Kenta; Watarai, Masahisa (Frontiers in Cellular and Infection Microbiology, 2021)
Francisella tularensis, the causative agent of tularemia, is transmitted by arthropod vectors within mammalian hosts. The detailed mechanisms contributing to growth and survival of Francisella within arthropod remain poorly understood. To identify novel factors supporting growth and survival of Francisella within arthropods, a transposon mutant library of F. tularensis subsp. novicida (F. novicida) was screened using an F. novicida–silkworm infection model. Among 750 transposon mutants screened, the mltA-encoding membrane-bound lytic murein transglycosylase A (MltA) was identified as a novel growth factor of F. novicida in silkworms. Silkworms infection with an mltA deletion mutant (ΔmltA) resulted in a reduction in the number of bacteria and prolonged survival. The ΔmltA strain exhibited limited intracellular growth and cytotoxicity in BmN4 silkworm ovary cells. Moreover, the ΔmltA strain induced higher expression of the antimicrobial peptide in silkworms compared to the wild-type strain. These results suggest that F. novicida MltA contributes to the survival of F. novicida in silkworms via immune suppression-related mechanisms. Intracellular growth of the ΔmltA strain was also reduced in human monocyte THP-1 cells. These results also suggest the contribution of MltA to pathogenicity in humans and utility of the F. novicida–silkworm infection model to explore Francisella infection.